A Prospective Multicenter Randomized Controlled Study on Interleukin‐6 Removal and Induction by a new Hemodialyzer With Improved Biocompatibility in Hemodialysis Patients: A Pilot Study. Issue 6 (8th August 2016) - Kakuta, Takatoshi; Komaba, Hirotaka; Takagi, Nobuyoshi; Takahashi, Yuichiro; Suzuki, Hajime; Hyodo, Toru; Nagaoka, Mikako; Tanaka, Reika; Iwao, Soichiro; Ishida, Mari; Kobayashi, Hiroyuki; Saito, Akira; et al.
Abstract: We compared interleukin‐6 (IL‐6) removal and induction between conventional polysulfone (Con) and TORAYLIGHT NV (NV) dialyzers in hemodialysis patients. Twenty patients on Con with high IL‐6 concentrations (2.7–8.5 pg/mL) were randomized to Con or NV group. Dialyzer performance was determined in NV group while patients were on Con and after being switched onto NV. Erythropoiesis‐stimulating agent (ESA) response index (ERI) was assessed every 4 months for one year. IL‐6 clearance was comparable between Con and NV. IL‐6 removal rates were comparable for the first 1 h, but were higher with NV for the entire session ( P  = 0.03). Before‐to‐during‐dialysis IL‐6 concentration ratios were lower with NV on the venous side after the session ( P  = 0.03). During the one‐year study, hemoglobin was lower in Con group than in NV group at month 8 ( P  = 0.046). ERI decreased in NV and increased in Con group, with a significant difference between the groups ( P  = 0.002). NV and Con are comparable in removing IL‐6 and both induce IL‐6. However, the data suggest that NV induces less IL‐6, which may reduce the risk of ESA hyporesponsiveness.